Instilling The Conservation Character Through Reconstruction of Scientific Knowledge Based on Local Wisdom - Riva Ismawati; Eko Juliyanto; Setiyo Prajoko; Eva Rahayuningsih (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
The purpose of this study is to reconstruct scientific knowledge based on local wisdoms of the Ngargomulyo village people in preserving the environment as a means to instill and enhance the conservation caracter for prospective science teachers. The research is a qualitative study of ethnosains, which means the study of an organized system of knowledge from the culture and local wisdoms of a community. The research subjects are the residents of Ngargomulyo village. The focus of the research is the value of environmental preservation which is manifested in the behavior patterns of the people of Ngargomulyo village. The data collection is done through interviews and in-depth observation. The data obtained is then verified, reconstructed, formulated, and conceptualized into the scientific knowledge. The results of the study indicate that efforts made by the people to preserve the surrounding environment are manifested in farming, raising livestock, forest activities, and sand and stone mining activities. In addition, the activities to protect the environment for natural conservation are also evident from the efforts to maintain spring water sources. The environmental preservation messages are also found on some boards installed in certain places.Keywords: conservation character, local wisdoms, Ngargomulyo village